Varicella zoster virus infection after allogeneic hematopoietic cell transplantation in children using a relatively short duration of acyclovir prophylaxis: A retrospective study. Issue 14 (April 2017) - Han, Seung Beom; Kim, Seong koo; Lee, Jae Wook; Lee, Dong-Gun; Chung, Nack-Gyun; Jeong, Dae Chul; Cho, Bin; Kang, Jin-Han
Abstract : Abstract: Although acyclovir prophylaxis against varicella zoster virus (VZV) infection for ≥1 year is recommended after allogeneic hematopoietic cell transplantation (HCT), the emergence of acyclovir-resistant viruses and adverse drug effects cannot be ignored. We investigated the cumulative incidence of VZV infection after allogeneic HCT in children receiving a shorter duration of acyclovir prophylaxis than recommended and evaluated the appropriateness of the short duration of acyclovir prophylaxis. Medical records of 217 children who received allogeneic HCT were retrospectively reviewed until a median of 25 months (range = 1–59 months) after HCT. Acyclovir prophylaxis was given for a median of 9 weeks (range = 3–24 weeks) after HCT. VZV infection was diagnosed in 33 (15.2%) children at a median time of 5 months (range = 2–41 months) after HCT. The 1-year and 2-year cumulative incidences of VZV infection after allogeneic HCT were 11.2% and 15.5%, respectively. These incidences were between the previously reported 1-year incidence of 25% to 30% in patients not receiving prophylaxis and 1-year incidence of 4% to 5% in patients receiving ≥1 year duration of prophylaxis. Male sex and older age were significantly associated with VZV infection after allogeneic HCT. Only 1 chickenpox patient experienced severe complications because of VZV infection, and there were no deaths attributable to VZV infection. In conclusion, a shorter duration of acyclovir prophylaxis may be appropriate for children receiving allogeneic HCT, based on the rare occurrence of severe complications because of VZV infection and the expected discomfort because of daily oral medication for a long time.